ChemInform Abstract: Gallium‐Indium Ordering in the Complex [Ni2Ga3In] Network of GdNi2Ga3In. Issue 41 (September 2016) - Galadzhun, Yaroslav V.; Horiacha, Myroslava M.; Nychyporuk, Galyna P.; Rodewald, Ute Ch.; Poettgen, Rainer; Zaremba, Vasyl I.
Abstract: The isotypic compounds LnNi2 Ga3 In (Ln: Y, Gd—Tm) are prepared by arc‐melting of the elements and characterized by powder XRD.